Turning Shoppers Into Buyers: How Brand Gestalt Drives Purchase Intention - Jessica Agnes Walewangko; Deske W. Mandagi; Indrajit Indrajit (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: This study aims to investigate the influence of brand gestalt on customer purchase intention in the context of fashion products, addressing the gap in understanding how the 4S brand gestalt dimensions (i.e., storyscape, sensescape, services cape, and stakeholders cape) directly impact consumer purchase intention in an increasingly competitive and dynamic fashion market. Methodology/Approach: This study employed a descriptive, causal, and quantitative research design, and data were collected through questionnaires distributed to 183respondents who were customers of popular fashion brands. The collected data were then analyzed using structural equation Modeling with the assistance of SmartPLS statistical software. Results/findings: The research findings indicate that all four dimensions of brand gestalt—story cape, senses cape, services cape, and stakeholder’s cape—have a significant positive influence on customer interest in purchasing fashion products. Limitations: One potential limitation of the study is that the respondents were H&M product customers in Manado, which may restrict the generalizability of the findings to a broader consumer population. Contribution: The theoretical implications of this study underscore the importance of maintaining a consistent and integrated brand gestalt to enhance consumers’ purchase interest in fashion products.